The Past as a Means of Persuasion: Visual Political Rhetoric in Finnish Dairy Product Advertising - Hakoköngäs, Eemeli; Sakki, Inari (Journal of Social and Political Psychology, 2019)
This study investigates the role of advertising and visual rhetoric in political persuasion. Analysis of Finnish dairy product video advertisements from 2010–2016 focuses on those that exploit time as the main reference framework. A better understanding of how advertising is used as a tool of political persuasion is sought by exploring the following questions: How are advertisements used in political communication? How is time used as a means of persuasion in advertising? What role do visual rhetoric and social representations have in the process of persuasion? The analysis shows how advertisements objectify work as a tradition and anchor it as a Finnish value. The results show how advertisements employ enthymeme as a major rhetorical tool to assert that the tradition of Finnish employment is under threat but the consumption of Finnish dairy products and favouring a pro-agrarian policy would ensure that the tradition is transmitted to new generations. The contributions of the study are twofold: First, the combination of social representations theory and classic rhetoric provides a theoretical and analytical perspective for the analysis of visual rhetoric in political persuasion. Secondly, by exploring the advertisements as political communication, the study shows how commercials are used to advocate ideological and political projects, such as certain kind of agricultural policy – an angle largely overlooked in the previous research of social and political psychology.